Nachweis des Plasmavolumenexpanders Hydroxyethylstärke in Humanurin - Thevis, M.; Opfermann, G.; Schänzer, W. (Deutsche Zeitschrift für Sportmedizin, 2001)
Since January 2000, plasma volume expanders like hydroxyethyl starch (HES) have been banned by the International Olympic Committee (IOC). The therapeutic administration is indicated in cases of hypovolaemic shocks and disturbances in capillary blood circulation. In endurance sports it is claimed to be used to elevate the amount of body fluid and to decrease hematocrit and hemogobine values. The determination of administered HES for doping analysis purposes is performed by means of two methods, which consist of the degradation of the polymer and subsequent derivatization of the resulting monomers. In a rapid screening procedure the per-trimethylsilyl derivatives of glucose and hy-droxyethylated glucose (HEG) are generated which are analysed by gas chromatography and mass spectrometry. Here, the exogenous mono-saccharides of 2- and 3-HEG are identified by the unambiguous fragment ions m/z 235, 248 and 261. The proof of the polysaccharide structure of the metabolites of HES is given by a confirmation method based on the degradation and derivatization to partially methylated alditol acetates (PMAAs). The free hydroxy groups of the polymer are methylated, the polysaccharide is hydrolysed, the resulting monosaccharides reduced to the corresponding alditols, the hydroxy groups of which are finally acetylated. The generated products are analysed and identified by means of gas chromatography and mass spectrometry. By means of these two methods six athletes participating at the 2001 nordic world championships in Lahti (Finland) could be convicted of using HES.